Exerkines and osteoarthritis - Jia, Shuangshuo; Yu, Ziyao; Bai, Lunhao (Frontiers in Physiology, 2023)
Osteoarthritis (OA) is the most prevalent chronic joint disease, with physical exercise being a widely endorsed strategy in its management guidelines. Exerkines, defined as cytokines secreted in response to acute and chronic exercise, function through endocrine, paracrine, and/or autocrine pathways. Various tissue-specific exerkines, encompassing exercise-induced myokines (muscle), cardiokines (heart), and adipokines (adipose tissue), have been linked to exercise therapy in OA. Exerkines are derived from these kines, but unlike them, only kines regulated by exercise can be called exerkines. Some of these exerkines serve a therapeutic role in OA, such as irisin, metrnl, lactate, secreted frizzled-related protein (SFRP), neuregulin, and adiponectin. While others may exacerbate the condition, such as IL-6, IL-7, IL-15, IL-33, myostatin, fractalkine, follistatin-like 1 (FSTL1), visfatin, activin A, migration inhibitory factor (MIF), apelin and growth differentiation factor (GDF)-15. They exerts anti-/pro-apoptosis/pyroptosis/inflammation, chondrogenic differentiation and cell senescence effect in chondrocyte, synoviocyte and mesenchymal stem cell. The modulation of adipokine effects on diverse cell types within the intra-articular joint emerges as a promising avenue for future OA interventions. This paper reviews recent findings that underscore the significant role of tissue-specific exerkines in OA, delving into the underlying cellular and molecular mechanisms involved.